The Relationship between Uric Acid Levels and Fatigue in Gout Arthritis Patients at the Sawah Besar Community Health Center, Central Jakarta - Setiawan, Suci; Mustafida, Ika; Juliani, Enni (LPPM Universitas Dhyana Pura, 2025)
Gout Arthritis is an inflammatory joint disease caused by the accumulation of uric acid crystals due to impaired purine metabolism. In addition to causing joint pain and swelling, this condition also has an impact on fatigue which can reduce the quality of life of sufferers. High uric acid levels contribute to chronic inflammation that can impair muscle function, decrease energy, and worsen fatigue both physically and psychologically. However, there have been few studies that specifically examine the relationship between uric acid levels and fatigue, especially at the primary health care level such as community health centers. This study used a quantitative approach with a cross-sectional design. A total of 79 respondents with Gout Arthritis at the Sawah Besar Community Health Center were selected using a purposive sampling technique. Uric acid level data were obtained through direct examination using the point of-care uric acid test, while fatigue was measured using the Multidimensional Fatigue Inventory (MFI-20) questionnaire. The relationship between variables was analyzed using the Pearson correlation test. The results showed that the majority of respondents experienced hyperuricemia and moderate to high levels of fatigue. The results of the correlation test showed a significant relationship between uric acid levels and fatigue with a p-value (0.018) and r value = 0.267 which indicates that the higher the uric acid levels, the higher the fatigue experienced by sufferers, these results confirm the importance of managing other factors such as pain, sleep quality, and stress in nursing management of Gout patients.